Crelier, Andrés. Introducción a la filosofía hermenéutica del lenguaje. (2015)
Crelier, Andrés. Introducción a la filosofía hermenéutica del lenguaje. Ciudad Autónoma de Buenos Aires: Biblos, 2013. 285 pp.